(untitled) (Journal of actual problems of jurisprudence, 2018)
The article considers the legal nature of corporate disputes. The author gives the definition of the concepts of «corporate conflict» and «corporate dispute» with the latest changes in procedural law, resulting in a general characterization of regulatory proceedings in corporate disputes. Key words: corporate legal relation, corporate conflicts, corporate disputes, protection of rights, legal regulation of proceedings in corporate disputes.